Peggy Mohan’ Deeda: Feminism Decoded - ., Hemika; Mishra, Parul (South Eastern European Journal of Public Health, 2025)
Peggy Mohan’s most significant text Jahajin offers an acute exploration of identity, gender, and social constraints through the character of Deeda, a woman who challenges marriage, patriarchy, and social expectations. This paper examines how the character of Deeda represents feminist ideals, and her empowerment through language, focusing on her resistance to traditional gender roles and her eventual self-discovery. By analysing Deeda’s struggle with the limitations placed on her by patriarchal society and her continually evolving relationship with her husband. This paper argues how women can redefine their relationships and identities with oppressive structures, additionally, Mohan represents a distinct portrayal of feminism which highlights the intersectionality of class, caste, and gender. Through the feminist lens, this research exhibits how Mohan’s works and women's characters critique patriarchal norms and offer a vision that redefines femininity and women’s roles in both public and private spheres. (Mohan, 2007)